Analysis of Hemostasis Blood Examination in Patients with Leukemia at Santa Elisabeth Hospital Medan - Ruth Agree Kartini Sihombing; Rica Vera Br Tarigan (Sean Institute, 2023)
Blood cancer or commonly reffered to as leukemia is a malignant disease of white blood cells originating from the bone marrow. To determine if someone has leukemia, it can be done by analyzing the results of a complete blood count. The research method is descriptive qualitative from secondary data taken from the medical records of Santa Elisabeth Hospital Medan for the period 2016-2023. Hemostasis analysis of 33 samples, the leukocyte count was obtained with the highest value above normal 76% (n=25). Count the type of platelet value with the highest value below normal 88% (n=29) and erythrocyte with the highest value below normal 94% (n=31). Abnormal value of hemaglobin level 100% (n=33). Hematocrit abnormal value 100% (n=33). LED with the highest abnormal value obtained 91% (n=30). Bleeding time normal value 100% (n=33). Blood clotting time normal value 100% (n=33). D-Dimer normal values were 51% (n=17) and abnormal values were 49% (n=16). PTT with the highest abnormal value was 79% (n=26). APTT normal value is 58% (n=19) and abnormal value is 42% (n=14). TT abnormal value 100% (n=33). Analysis of hemostasis in patients with leukemia at Santa Elisabeth Hospital Medan obtained that the number of erythrocytes, platelets, hemoglobin levels, hematocrit, blood sedimentation rate was low while the number of leucocytes was found high. The results of examination of bleeding time and blood clotting time were found normal, D-Dimer and APTT were found normal and some were found abnormal, the results of PTT were mostly found abnormal and TT overall abnormal.